Revisiting Basic Chemistry Curriculum to Foster Adaptive Learning in Higher Education - Nabuasa, Desi; Rochintaniawati, Diana; Riandi, Riandi; Sopandi, Wahyu; Wiji, Wiji (Universitas Negeri Semarang, 2024)
The transformation of higher education in Indonesia presents challenges and opportunities for universities to develop adaptive learning ecosystems. This study aims to analyze the Semester Learning Plans (RPS) of Basic Chemistry courses to evaluate their alignment with digital-era learning needs. Using a qualitative approach, the research involves document analysis of 19 RPS, focusing on learning methods and the integration of digital technology. Data were validated through questionnaires distributed to lecturers in charge of these courses. Results reveal that active learning methods, such as Problem-Based Learning (PBL) and Project-Based Learning (PjBL), dominate, yet the integration of innovative technologies like virtual laboratories and software-based simulations remains limited. The study highlights the importance of adaptive learning strategies, digital literacy, and culturally responsive teaching to support global demands. New findings emphasize the need for systematic lecturer training and institutional support to enhance technological adoption in teaching. This research contributes to the development of more effective and inclusive learning environments, benefitting both science education and society.